Interview with Annada Shankar Roy on Bangladesh liberation war of 1971, interviewed by Kabir in Calcutta - Kabir, Shahriar.
Interview with Annada Shankar Roy on Bangladesh liberation war of 1971, interviewed by Kabir in Calcutta.